2021
DOI: 10.1097/md.0000000000025097
|View full text |Cite
|
Sign up to set email alerts
|

Use of Shenhuang paste on Shenque point improves chemotherapy induced gastrointestinal toxicity in breast cancer

Abstract: Background: Breast cancer, a malignant disorder, occurs in the epithelial tissue of the breast gland. Chemotherapy is the standard treatment for breast cancer, however, the side effect, especially gastrointestinal dysfunction, due to chemotherapy still remain major problems. Traditional Chinese Medicine has been proven therapeutically effective on reducing adverse effects caused by chemotherapy. Shenhuang Plaster Methods: The study is a randomized, placebo-controlled, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Acupuncture is an important complementary therapy used in cancer treatment, Xu et al found that acupuncture treatment can inhibit the development of osteosarcoma by regulating intestinal microbiome [30]. What's more, in a randomized, placebo-controlled, blind trial, Wang et al observed that Shenhuang plaster application could relieve chemotherapy-induced gastrointestinal toxicity in breast cancer patients [31]. Additionally, gut microbiota promotes the maintaining of health and acts as adjuvants in the treatment of cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is an important complementary therapy used in cancer treatment, Xu et al found that acupuncture treatment can inhibit the development of osteosarcoma by regulating intestinal microbiome [30]. What's more, in a randomized, placebo-controlled, blind trial, Wang et al observed that Shenhuang plaster application could relieve chemotherapy-induced gastrointestinal toxicity in breast cancer patients [31]. Additionally, gut microbiota promotes the maintaining of health and acts as adjuvants in the treatment of cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…The scoping review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. 20 …”
Section: Methodsmentioning
confidence: 99%
“…The overall concordance rate was very low, notably in reporting the formula’s profile in safety and quality. There was very low concordance at 5% (1/22) with reporting the formula’s safety assessment, 37 9% (2/22) with reporting the quality control of each ingredient and the formula as a whole, 20 , 37 0% (0/22) with reporting the production method of the formula, and 5% (1/22) with reporting the authentication method of each ingredient. 37 There was very low concordance with reporting the formula’s details of administration such as dosage at 5% (1/22), fair concordance with reporting administration route at 50% (11/22), low concordance with reporting dosage form at 23% (5/22), and low concordance with reporting substance name 36% (8/22).…”
Section: Overall Concordancementioning
confidence: 99%
“…Therefore, a better understanding of the gastrointestinal microflora in SDD has been of great significance. Acupoint application therapy is the application of Chinese herbal medicine to the corresponding points to regulate meridians, yin and yang, and qi as well as the blood of the human body [ 8 ]. The Shenque point has a thin cuticle making it conducive to rapid drug absorption, and its location close to the intestinal tract strengthens the spleen and stomach by promoting the flow of Qi and relaxing the bowels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%